Parametric study on the impact of traffic- induced vibrations on residential structures in Istanbul, Turkey - Yesilyurt, A.; Akram, M. R.; Zulfikar, A. Can; Alcik, H. (Techno-Press, 2024)
Traffic-induced vibrations (TIVs) possess the potential to induce structural damage in both historical and critical edifices. Recent investigations have underscored the adverse impact of TIVs within buildings, manifesting as a deleterious influence on the quality of life and operational efficiency of occupants. Consequently, these studies have dichotomized TIVs into two primary limit categories: the threshold for vibrations capable of causing structural damage and the limit values associated with human comfort. In this current research endeavor, an exhaustive analysis of peak ground acceleration (PGA), peak ground velocity (PGV), peak ground displacement (PGD), and the frequency spectrum of ground motions originating from diverse traffic sources has been conducted. Furthermore, the detrimental repercussions of these vibrations on structures, gauged through the assessment of the peak particle velocity (PPV) parameter, have been systematically evaluated. The findings of this study elucidate that TIVs within the examined structures do not attain magnitudes conducive to structural compromise; however, the levels surpassing human comfort limits are evident, attributable to specific sources and distances. Moreover, this investigation sheds light on the absence of comprehensive criteria and guidelines pertaining to the assessment of TIVs in structures within the Turkish Building Seismic Design Code 2018. It seeks to raise awareness among building constructors about the critical importance of addressing this issue, emphasizing the imperative for guidelines in mitigating the impact of TIVs on both structural integrity and human well-being.
Keywords: fourier spectrum; human comfort limits; peak particle velocity; traffic-induced vibrations